2008
DOI: 10.1177/1524839907309044
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Syndrome Prevention Using Community-Based Narrowcasting Campaigns

Abstract: Preventing fetal alcohol syndrome (FAS) by encouraging pregnant women to abstain from drinking alcohol competes with commercial alcohol marketing. Two FAS-prevention campaigns using a narrowcast approach among young women of childbearing age in two disadvantaged Southern California communities are compared. The design, implementation process, and degree to which campaigns reached the priority populations are the focus of this article. Formative research shows that young women in disadvantaged communities recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…Specifically, we prioritized building community demand for healthy fruits and vegetables by using a small media or narrowcast approach to attract new store patrons as well as to tout ongoing benefits of shopping local and learning to eat healthy [17]. For example, in addition to changing products sold and the physical appearance of each store, we also had ongoing activities such as cooking demonstrations and other community events.…”
Section: A Multi-level Corner Store Intervention In a Food Swampmentioning
confidence: 99%
“…Specifically, we prioritized building community demand for healthy fruits and vegetables by using a small media or narrowcast approach to attract new store patrons as well as to tout ongoing benefits of shopping local and learning to eat healthy [17]. For example, in addition to changing products sold and the physical appearance of each store, we also had ongoing activities such as cooking demonstrations and other community events.…”
Section: A Multi-level Corner Store Intervention In a Food Swampmentioning
confidence: 99%
“…A three-wave repeated cross-sectional survey showed that the knowledge scores of African American teens increased significantly after the campaign. Glick, Prelip, Myerson, and Eilers (2008) compare the results of two FASD prevention campaigns targeting young women of childbearing age in two disadvantaged Southern California communities. Results of the evaluation survey showed that a social norms approach using positive role models was the most acceptable message strategy.…”
Section: Alcohol Consumption Among Pregnant Womenmentioning
confidence: 99%
“…By profiling the context of the behaviour, and the knowledge, attitudes, beliefs, expectancies, and motivations of the target audience in terms of theoretical constructs, the effectiveness of message strategies can be strengthened. Although a number of qualitative and quantitative studies have provided insights into women's knowledge, beliefs, and attitudes with regards to alcohol use during pregnancy (Balachova, Bonner, Isurina, & Tsvetkova, 2007;Baxter, Hirokawa, Lowe, Nathan, & Pearce, 2004;Kesmodel & Kesmodel, 2002;Raymond, Beer, Glazebrook, & Sayal, 2009;Toutain, 2010), few describe formative research with the target audience that was used to develop message strategies aimed at preventing prenatal alcohol exposure (Branco & Kaskutas, 2001;Glik, Prelip, Myerson, & Eilers, 2008;Mengel, Ulione, Wedding, Jones, & Shurn, 2005).…”
Section: Introductionmentioning
confidence: 99%